The Work-life Balance on Civil Servants Performance through Organizational Commitment as a mediator - Immanuel Setiapati Saka Soebagijo (Jurnal Manajemen Sains dan Organisasi, 2023)
Objectives – This study aims to provide an empirical explanation of the influence of the work-life balance on civil servants performance with organizational commitment as a mediating variable. Design/Methodology/Approach – This  study  used  a  saturating  sample  size  of  59 sample  from  the Central Borneo Regional Development Planning and Regional Research and Development Agency  as  its  unit  of analysis. SmartPLS 4.0.9.5 was used to perform a Likert-scale analysis on the gathered data. Findings – The results showed that the Work-life Balance has a significant effect on the performance of the employees, and the Organizational Commitment variable has a significant effect in strengthening the relationship between Work-life Balance and the Performance of employees. Conclusions and Implications - Work-life balance directly or through organizational commitment has a positive influence on ASN performance. Bappedalitbang of Central Kalimantan Province can maintain work-life balance and maintain organizational commitment to improve ASN performance.